1977
DOI: 10.1246/cl.1977.1137
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Behavior of Tetrasulfonated Metal Phthalocyanines in the Reduction of Carbon Dioxide

Abstract: In the electroreduction of carbon dioxide, catalytic activities of the tetrasulfonated metal phthalocyanines(MeTSP) homogeneously dissolved in the Clark–Lubs buffer solutions were investigated by the measurements of current- and capacitance-potential curves. It was found that CoTSP and NiTSP were active but not CuTSP and FeTSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 1 publication
2
34
0
1
Order By: Relevance
“…0.3 V more negative than the thermodynamic C021 CO redox potential. Oxalate and formate were also detected in the solution, as was previously reported, 102,126 but in only trace amounts, and the major product was gaseous CO. The tumover numbers of the catalyst exceeded 100 s-t, and the dinegative state of Co-Pc was again suggested to be the active form.…”
Section: Metal Complexes Of N-macrocyclessupporting
confidence: 82%
See 1 more Smart Citation
“…0.3 V more negative than the thermodynamic C021 CO redox potential. Oxalate and formate were also detected in the solution, as was previously reported, 102,126 but in only trace amounts, and the major product was gaseous CO. The tumover numbers of the catalyst exceeded 100 s-t, and the dinegative state of Co-Pc was again suggested to be the active form.…”
Section: Metal Complexes Of N-macrocyclessupporting
confidence: 82%
“…Hiratsuka et al 102 used water-soluble tetrasulfonated Co and Ni phthalocyanines (M-TSP) as homogeneous catalysts for CO2 reduction to formic acid at an amalgamated platinum electrode. The current-potential and capacitance-potential curves showed that the reduction potential of CO2 was reduced by ca.…”
Section: Metal Complexes Of N-macrocyclesmentioning
confidence: 99%
“…This article must therefore be hereby marked "advertisement" in accordance with 18 U. S. C. §1734 solely to indicate this fact. On the other hand, metal complexes in general, and cobalt complexes in particular, are able to bind CO2 (24)(25)(26)(27)(28)(29)(30)(31)(32) and to act as electrocatalysts for its reduction (33)(34)(35)(36), for instance to CO by the overall reaction 4 (36).…”
mentioning
confidence: 99%
“…A promising option appears to be the metal–nitrogen–carbon (M‐N‐C) electrocatalysts. Although they were first investigated in the 1970s as porphyrins and phthalocyanines, the interest in carbon‐based compounds for CO 2 RR only recently grew. Throughout the last years, pyrolyzed carbonaceous materials doped with nitrogen (i.e., N‐C electrocatalysts) or doped with nitrogen and 3d transition metals (i.e., M‐N‐C electrocatalysts) were widely investigated for the ORR and CO 2 RR …”
Section: Co2 Valorization and Syngas Generationmentioning
confidence: 99%
“…Thus, one should investigate electrocatalysts based on abundant,i nexpensive elements that generate 50 %C O/H 2 at low overpotentials without leadingt ot he formation of other carbon-basedp roducts.A promising option appears to be the metal-nitrogen-carbon (M-N-C)e lectrocatalysts. Although they were first investigated in the 1970s as porphyrins and phthalocyanines, [36,37] the interest in carbon-based compounds for CO 2 RR only recently grew. Throughout the last years, pyrolyzed carbonaceous materials doped with nitrogen (i.e.,N -C electrocatalysts)o rd oped with nitrogen and 3d transition metals (i.e., M-N-Ce lectrocatalysts) were widely investigatedf or the ORR [38][39][40][41] and CO 2 RR.…”
mentioning
confidence: 99%